Comparison of Flake ice and Gel ice in the Preservation of Lethrinus lentjan (Lacepede, 1802) Fillets - Hassan, Femeena; Joshy, C. G. (Fishery Technology, 2018)
Effectiveness of different icing, gel ice and flake ice in extending the shelf life of fish fillets (Lethrinus lentjan) (Lacepède, 1802) was evaluated. Samples were taken from preserved samples at two days intervals for organoleptic, biochemical and microbiological analysis up to 16 days of storage. Based on t-test, the biochemical variables viz., pH, Total Volatile Base Nitrogen (TVB-N) and Trimethylamine Nitrogen (TMA-N), ThioBarbituric Acid Value (TBA) Free Fatty Acid (FFA) and Peroxide value (PV) showed a significant difference between two methods of icing at. Organoleptic scores for appearance colour, odour, texture and overall acceptability were tested. The results revealed that there was no significant difference between two methods of icing at 5% level of significance during storage, but the significant difference noticed at 10% level of significance. Based on the biochemical and organoleptic analysis, it is inferred that gel icing was better than flake ice storage for storage up to 8 days. Simple linear regression model (significant R2 value) to the experimental data of both type of icing to quantify the rate of change which indicated a significant increase in the quality indices as the storage days increased. On the other hand the rate of increase of biochemical quality indices was minimum for samples stored in flake ice.